2018
DOI: 10.1007/s40844-018-0120-y
|View full text |Cite
|
Sign up to set email alerts
|

Gravity modeling in social science: the case of the commuting phenomenon in Greece

Abstract: This article empirically examines the utility of the gravity modeling in regard to its explanatory resolution, to its power against linearity, and to its geographical scale (intercity vs. interregional). For this purpose, the analysis is performed towards three directions; the first regards the model structure and examines how the number of explanatory variables (drafted from a pool of available predictors) affects the model determination, the second examines the model type, comparing the same predictor config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Subsequently, Varga [3] proposed a further generalization for the original radiation model-flow and jump model (FJM); test results showed that the FJM can offer an improved description for commuting data. Despite some limitations of the previous models [4][5][6][7][8][9], these models are widely used due to the advantages in approaching the mobility laws [6]. Some studies try to investigate the commuting pattern considering the stop-making behavior or land use properties.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Varga [3] proposed a further generalization for the original radiation model-flow and jump model (FJM); test results showed that the FJM can offer an improved description for commuting data. Despite some limitations of the previous models [4][5][6][7][8][9], these models are widely used due to the advantages in approaching the mobility laws [6]. Some studies try to investigate the commuting pattern considering the stop-making behavior or land use properties.…”
Section: Introductionmentioning
confidence: 99%